Main differential endometrial microbiota associated with recurrent implantation failure: a case control study - Gao, Hong; Xiao, Jing; Liang, Bingyan; Wang, Xiaolan; Li, Huanhuan; Li, Genlin; Wu, Baoyu (Frontiers in Endocrinology, 2025)
IntroductionRecurrent implantation failure (RIF) is a major challenge in reproductive medicine, and emerging evidence suggests that alterations in the endometrial microbiota may play a critical role in its pathogenesis. To identify the main differential endometrial microbiota associated with RIF and to establish threshold values for their relative abundance.MethodsThis case-control study was conducted in the Departments of Obstetrics, Gynecology, and Reproductive Medicine at two large hospitals. From March to December 2023, the study recruited 17 infertile patients with RIF (Group A, cases), 19 healthy non-pregnant women (Group B, controls), and 20 healthy pregnant women (Group C, controls). Demographic information, medication history, clinical data, and endometrial tissue samples were collected. Endometrial microbiota of all participants was profiled using 16S rRNA gene sequencing.ResultsThe richness of endometrial microbiota in Group A was significantly lower compared to both control groups (P=0.013, P=0.022, respectively). The diversity of endometrial microbiota in Group A and B was significantly higher compared to Group C (P=0.043, P=0.002, respectively). The composition of endometrial microbiota in Group A differed significantly from both control groups, whereas only minor differences were observed between the two control groups (PERMANOVA, P=0.001). Methyloversatilis, Lactobacillus, Sphingomonas, Faecalibacterium, Escherichia-Shigella, Bacteroides, and Aeromonas were identified as the main differential endometrial microbiota associated with RIF, with threshold relative abundances of 3.807%, 6.606%, 0.192%, 0.193% , 0.618%, 2.411%, and 0.019%, respectively. In Group A, Lactobacillus was positively correlated with Sphingomonas (r=0.64, P=0.005).DiscussionMethyloversatilis, Lactobacillus, Sphingomonas, Faecalibacterium, Escherichia-Shigella, Bacteroides, and Aeromonas were the main differential endometrial microbes associated with RIF. Preliminary threshold values for their relative abundances were established.